A case study of healthcare services in Lurwaryizo, Mbhashe Local Municipality, Eastern Cape Province - Chidy Akunwafor; Musa Zuma; Iyabo Obasanjo (Taylor & Francis Group, 2024)
As part of the strategy by the local municipal government to improve health services in Lurwaryizo community in Mbhashe Local Municipality in Eastern Cape province of South Africa, an investigation of the current healthcare delivery available to the community was implemented. A qualitative study using Focused Group Discussions (FGDs) on 12 recently trained Community Health Workers (CHWs), Community members in the 8 villages of the area, and 15 Traditional Medical Practitioners (TMPs), and an interview with the nurse who runs the only health center in the area was carried out. Our findings indicate that the overall healthcare delivery in the area is poor due to health manpower shortages and that CHWs and TMPs are currently indispensable to providing primary health care in the community. Compensation of CHWs is a major issue although their services were valued by their supervisor at the only health clinic. The involvement of local community participation in determining healthcare priorities will aid improved healthcare delivery, as well as more effective use of TMPs and CHWs. Recommendations for improving health in the community were also provided such as provision of health promotion services by CHWs and creating a cross-referral system with the formal health system for TMPs.